2016
DOI: 10.1080/13607863.2016.1255716
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver profiles in dementia related to quality of life, depression and perseverance time in the European Actifcare study: the importance of social health

Abstract: Differences exist between types of caregivers that explain variability in quality of life, depressive symptoms and perseverance time. Our findings may give direction for tailored interventions for caregivers of persons with dementia, which may improve social health and reduce health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
(52 reference statements)
2
31
0
Order By: Relevance
“…The different established caregiver profiles (Janssen, et al, 2017) have demonstrated their predictive value when examining dementia care use. The profiles include a broad range of information relating to the person with dementia and the informal caregiver, and therefore can provide useful information for professionals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The different established caregiver profiles (Janssen, et al, 2017) have demonstrated their predictive value when examining dementia care use. The profiles include a broad range of information relating to the person with dementia and the informal caregiver, and therefore can provide useful information for professionals.…”
Section: Resultsmentioning
confidence: 99%
“…The two low strain groups have in common at baseline (Janssen, et al, 2017) low levels of relative stress, higher levels of sense of coherence and a more internal locus of control, together with a higher proportion of care recipients with mild dementia and less neuropsychiatric symptoms. This profile, for both age groups, appears, over a 12-month period, to be associated with less risk of admission to hospital or care home , and lower uptake of home social care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations